2021
DOI: 10.3389/fmed.2020.595503
|View full text |Cite
|
Sign up to set email alerts
|

Survival Factors and Metabolic Pathogenesis in Elderly Patients (≥65) With COVID-19: A Multi-Center Study

Abstract: Background: Elderly patients infected with COVID-19 are reported to be facing a substantially increased risk of mortality. Clinical characteristics, treatment options, and potential survival factors remain under investigation. This study aimed to fill this gap and provide clinically relevant factors associated with survival of elderly patients with COVID-19.Methods: In this multi-center study, elderly patients (age ≥65 years old) with laboratory-confirmed COVID-19 from 4 Wuhan hospitals were included. The clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 42 publications
1
18
0
6
Order By: Relevance
“…Consistently, previous studies comparing metabolites from patients with different ARDS categories and healthy controls revealed that the concentration of phenylalanine signi cantly increased in patients with ARDS and tended to change in response to the severity of ARDS [13]. Phenylalanine metabolism was highly upregulated in the deceased subgroup [37]. Phenylalanine levels were also associated with ARDS caused by H1N1 pneumonia by resultant viral and bacterial infections [9].…”
Section: Discussionsupporting
confidence: 77%
“…Consistently, previous studies comparing metabolites from patients with different ARDS categories and healthy controls revealed that the concentration of phenylalanine signi cantly increased in patients with ARDS and tended to change in response to the severity of ARDS [13]. Phenylalanine metabolism was highly upregulated in the deceased subgroup [37]. Phenylalanine levels were also associated with ARDS caused by H1N1 pneumonia by resultant viral and bacterial infections [9].…”
Section: Discussionsupporting
confidence: 77%
“…The same study also showed that inhibiting fatty acid synthesis by drugs, such as orlistat, lowered viral levels in the lung and increased survival in a mouse model. Interestingly, a study in elderly patients showed a lower metabolic flux in the fatty acid pathway in survivors vs the deceased [ 81 ]. A more detailed analysis at the level of a single fatty acid showed opposite changes in levels of different fatty acids in serum of patients with severe COVID-19 depending on the type of the fatty acid and its desaturation index [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the goals of this study, included articles was divided in 4 groups; PUFAs and risk of Covid-19 [26] , [27] , [28] , [29] , [30] , [31] , PUFAs and severity of Covid-19 [27] , [32] , [33] , [34] , [35] , [36] , [37] , PUFAs and Risk of Death Due to Covid-19 [3] , [26] , [29] , [32] , [38] , [39] , [40] and Covid-19 and receiving PUFAs [26] , [41] .…”
Section: Resultsmentioning
confidence: 99%
“…no significant differences in levels of PTT, hematocrit, neutrophil, monocyte, hemoglobin, and Plt - On the other blood factors: No significant differences in blood glucose, albumin, MAP, and O2 sat. Hamulka et al (2021) [26] Worldwide and Poland First wave: 2296 Second wave: 978 Online cross-sectional ≥18 (1) in April and May 2020 (2) in November 2020 during the second wave Good Spearman rank's coefficients Omega-3 fatty acids and Worldwide : COVID-19 cases: 0.06; Deaths: 0.06 Coronavirus relative search value (RSV): − 0.74; p ≤ 0.01 Poland: COVID-19 cases: 0.21; Deaths: 0.21, coronavirus relative search value (RSV): − 0.26 - Omega-3 fatty acids supplement consumption: increase from 2.8% to 8.2% Jontez et al (2021) [41] Slovenia 38 (14 m , 24 f) web survey 36.3 ± 10.1 December 2019 Fair Mean ± SD fatty acids intake ratio (PUFA+MUFA)/SFA) in healthy Adults: Baseline 1.98 ± 1.34, During Lockdown 1.77 ± 1.20 and Post-Lockdown 1.54 ± 0.78 Julkunen et al (2021) [42] UK Pneumonia participants : n = 105,142; 102,639 controls, 2507 severe incident cases COVID-19 Participants : n = 92,725; 92,073 control, 653 severe incident cases Retrospective cohort 49–84 blood samples collected 2007–2010 Good - multi-biomarker score for fatty acids and susceptibility to severe COVID -19: odds ratio 2.9 [95%CI 2.1–3.8] for highest vs lowest quintile; p-value<0.001 Mei et al (2021) [39] China 223: 91 discharged and 132 deceased multi-center study ≥65 years old Between January and March 2020 Good - Fatty acid: lower flux in the survivors vs. the deceased subgroup, AOR = 15.61 [95% CI: 6.66–36.6], p < 0.001. Nguyen et al (2021) [27] France 61: 34 non-COVID-19,27 COVID-19 prospective non-COVID-19: 69 (± 12) COVID-19: 62 (± 11) Good …”
Section: Resultsmentioning
confidence: 99%